Electrostatic biosorption of COD, Mn and H2S on EFB-based activated carbon produced through steam pyrolysis: an analysis based on surface chemistry, equilibria and kinetics - Amosa, Mutiu K.; Jami, Mohammed Saedi; Al-Khatib, Ma'an Fahmi Rashid (Springer Netherlands, 2016)
Biosorption of chemical oxygen demand (COD), manganese (Mn) and hydrogen sulphide (H2S) onto an empty fruit bunch (EFB)–based powdered activated carbon (PAC) from a multicomponent system—biotreated palm oil mill effluent (BPOME)—were studied in a batch adsorption process. The experimental results were fitted to four isotherm models, and four kinetic models. Amongst the isotherm models (Langmuir, Freundlich, Temkin and DubininRadushkevich) employed, Langmuir model showed the best conformity to the equilibrium data with R2 values of 1.00 for COD and 0.9999 for both Mn and H2S. The Dubinin–Radushkevich model followed the conformity trend with R2 values of 0.9984, 0.9948 and 0.9824 for COD, H2S, and Mn, respectively. Also, amongst the kinetic models (Pseudo-first order, Lagergren’s pseudo-second order, Elovich and Weber– Morris intra-particle diffusion) employed, only the pseudosecond order model could best describe the adsorption behaviours of all the three contaminants withR 2 values of 1.00 in all cases. The mechanistic uptake pathway was further examined by means of the Fourier transform infrared in studying the surface chemistry of the PAC. It was observed that the presence of functional groups like the aldehydes andketones, carbonyl, mono-alkyl, amines, amongst others led to physicochemical interactions between PAC surface and the contaminants. Overall, the equilibrium, kinetics and surface chemistry analyses pointed towards the adsorption processes been largely driven by electrostatic sorption. Additionally, the EFB-based PAC was capable of reducing COD, Mn and H2S from POME, hence, could be utilized in developing a unit operation for integration into the current POME treatment. Graphical Abstract Percent uptake versus adsorption time plot for COD, Mn and H2S removal from biotreated POME.